Evaluation of The Teaching Factory Program at SMK Pancasila 1 Kutoarjo (Educational Management, 2022)
The research aim to analyze teaching factory as product-based learning model that utilizes the synergy of schools with industry to produce graduates who are competent and in line with the needs of the business and industry world. The CIPP program evaluation model is designed to improve the program implementation system comprehensively so that it can be considered in the future for implementing the program. SMK Pancasila 1 Kutoarjo has implemented a teaching factory learning program in order to improve the competence of its students. This study uses a qualitative descriptive method, for data collection techniques using observation, interviews, and documentation. Researchers conducted interviews with school principals, program administrators, TBSM skill competency heads and teachers of automotive productive subjects at SMK Pancasila 1 Kutoarjo. The results of this study indicate that; (1) the results of the context evaluation regarding the implementation of the teaching factory learning program are in line with the school's vision, mission, and goals, (2) the results of the evaluation of inputs have gone well, 3) the results of the evaluation of the process in the teaching factory learning program have gone well because so far the learning process of the program has been running well according to the plan and has not encountered any significant obstacles; (3) the results of product evaluation in the implementation of the teaching factory learning program have gone well.